Sleep-disordered breathing in epilepsy: epidemiology, mechanisms, and treatment. Issue 4 (31st January 2018) - Sivathamboo, Shobi; Perucca, Piero; Velakoulis, Dennis; Jones, Nigel C; Goldin, Jeremy; Kwan, Patrick; O'Brien, Terence J
Abstract: Epilepsy is a group of neurological conditions in which there is a pathological and enduring predisposition to generate recurrent seizures. Evidence over the last few decades suggests that epilepsy may be associated with increased sleep-disordered breathing, which may contribute towards sleep fragmentation, daytime somnolence, reduced seizure control, and cardiovascular-related morbidity and mortality. Chronic sleep–disordered breathing can result in loss of gray matter and cause deficits to memory and global cognitive function. Sleep-disordered breathing is a novel and independent predictor of sudden cardiac death and, as such, may be involved in the mechanisms leading to sudden unexpected death in epilepsy. Despite this, the long-term consequences of sleep-disordered breathing in epilepsy remain unknown, and there are no guidelines for screening or treating this population. There is currently insufficient evidence to indicate continuous positive airway pressure (CPAP) for the primary or secondary prevention of cardiovascular disease, and recent evidence has failed to show any reduction of fatal or nonfatal cardiovascular endpoints. Treatment of sleep-disordered breathing may potentially improve seizure control, daytime somnolence, and neurocognitive outcomes, but few studies have examined this relationship. In this review, we examine sleep-disordered breathing in epilepsy, and discuss the potential effect of epilepsy treatments. We consider the role of CPAP and other interventions for sleep-disordered breathing and discuss their implications for epilepsy management.